An Overview on Rail Transit Energy Internet - DING Rongjun; ZHANG Zhixue; LI Hongbo (机车电传动)
Aiming at the problems of large energy consumption, serious emission, noise pollution and so forth brought by the rapid development of the rail transit transportation system, with internet concept introducing and adopting information communication technology (ICT) and intelligent methodology to subversively gentrify the rail transit development pattern, an idea wsa proposed to realize energy information fusion and develop a rail transit high-efficiency and clean energy internet which operated in an intelligent way of energy consumption, transmission and providing. Firstly, the fundamental architecture of rail transit energy internet in detail was described. Then, the technical characteristics, academic connotation and benefits were pointed out. Finally, the crucial technology chain of rail transit internet was introduced.